Academic Engagement of Blind Collage Students - Hilmi Yatun Solehah; Meydina Muharramah Putri Diliyanty; Angelina Kartini Agung Lestari; Rudi Cahyono (ASTEEC, 2023)
This study aims to describe the academic engagement of blind students at Universitas Airlangga. Airlangga University which has strived to become a disability-friendly campus by providing special facilities. The method used in this research is qualitative with a case study approach. Respondents in this study were blind students at Airlangga University who had academic and non-academic achievements. The results of the study show that the description of academic engagement of students with visual impairments at Universitas Airlangga consists of three aspects; 1) vigor is characterized by a sense of enthusiasm and enthusiasm in doing assignments, discussing, and trying new things; 2) absorption is marked by focusing on academic activities based on one's own initiative; 3) dedication is marked by his enthusiasm to inspire others not only domestically but also abroad, also being involved in activities related to his lectures, feeling satisfied and proud of his decision to study in that department. Their limitations do not become an obstacle for blind students to be involved in lectures.